Lonely places, dangerous ground : Nicholas Ray in American cinema - Rybin, Steven, 1979-; Scheibel, Will, 1983- (SUNY series, horizons of cinema., 2014)
"Examines the director's place in the history of Hollywood and the institution of cinema"--Provided by publisher